A nuclear magnetic resonance study of the dynamics of organofluorine interactions with a dissolved humic acid. (February 2016) - Longstaffe, James G.; Courtier-Murias, Denis; Simpson, Andre J.
Abstract: A quantitative understanding of the dynamics of the interactions between organofluorine compounds and humic acids will contribute to an improved understanding of the role that Natural Organic Matter plays as a mediator in the fate, transport and distribution of these contaminants in the environment. Here, Nuclear Magnetic Resonance (NMR) spectroscopy-based diffusion measurements are used to estimate the association dynamics between dissolved humic acid and selected organofluorine compounds: pentafluoroaniline, pentafluorophenol, potassium perfluorooctane sulfonate, and perfluorooctanoic acid. Under the conditions used here, the strength of the association with humic acid increases linearly as temperature decreases for all compounds except for perfluorooctanoic acid, which exhibits divergent behavior with a non-linear decrease in the extent of interaction as temperature decreases. A general interaction mechanism controlled largely by desolvation effects is suggested for all compounds examined here except for perfluorooctanoic acid, which exhibits a specific mode of interaction consistent with a proteinaceous binding site. Reverse Heteronuclear Saturation Transfer Difference NMR is used to confirm the identity and nature of the humic acid binding sites. Graphical abstract: Highlights: NMR diffusion measurements are used to quantify the association equilibrium between organofluorine compounds and humic acid. Most organofluorine compounds studied here exhibit stronger associations at lower temperatures. PFOA exhibits a non-linear and inverse relationship between association dynamics and temperature. PFOA associates only with proteinaceous components of humic acid.